"O jus de governar já não se herda": Manuel Odorico Mendes e seu projeto de nação brasileira (1825-1833) - Botelho, Yane Silva (2017)
This investigation of Manuel Odorico Mendes’ (1799-1864) conception of brazilian nation is centered in his journalistic and parliamentary action in the decisive years of 1825 to 1833. Its central aim is understand how the writer and public man had perceived and represented Brazil in that moment (at the rising of his journalistic carreer and at his first two elections to the National Assembly). Through the observation of the most important notes of the imperial state’s formation and the changing in the historic scope wich resulted from the abandon of the Portugal-Brazil unity – that had occasioned a search for a model of national representation, a search all the way fueled in the Regencial Period –, it is our objective to analyse the intelectual production (as journalist and, at some extent, as poet and translator) and political action of Odorico Mendes as symptons of his national project (wich brings in itself some idea of national indentity) at the new status quo of post-independency, an effort that we will carry out noting, from the especificity of Odorico Mendes’ position, the general problems of the contemporary public discussion. Too much proper of his carreer, as we will argument, is his constant oscilation between the defense of a modern european model of nation (based in liberal and iluminist ideas) and it’s adaptation to a radically different reality (the brazilian one), in a way that allways postponed the consolidation of the values most praised by the author of O Argos da Lei. Not a coincidence, altough a republican, Odorico Mendes made himself one of the pivotal responsible ones for Brazil continued monarchist regime after the April 7.